Benefits of providing videos on the resilience of adolescent girls regarding premarital sexual behavior - Ni Putu Risma Sintya Jayanti; Ni Wayan Armini; Ni Wayan Ariyani (Jurnal Kesehatan Ibu dan Anak, 2022)
The transition period in adolescents increased interest in sexuality can lead to premarital sexual intercourse. Adolescent need education about the resilience of premarital sex through videos. This study aims to determine the benefits of providing video on the resilience of adolescent girls regarding premarital sexual behaviour. The design used pre-experiment with pretest-posttest design. Implementation in March-April 2022 in PGRI 1 Amlapura Senior High School Karangasem Regency, Bali with a total sampling technique of Social and Language Class. The samples are 45 students. The research instrument used a youth resilience questionnaire. Normality test with Shapiro Wilk obtained data is not normally distributed. Analysis used the Wilcoxon test with a significance level of p-value <0.05. The results show the mean before giving a video is 68 and after giving a video the mean is 92. The results of the Wilcoxon test showed there was a significant benefit in giving video with a p-value of 0.001 < 0.05. The comparison of pretest and pottest of adolescent resilience was 44 respondents who had positive ranks and 1 person had ties. Adolescents with low resilience tend to have low self-esteem and pose unwanted risks. Researchers suggest that respondents can apply resilience directly.